PENGARUH SUBTITUSI TEPUNG TAPIOKA DAN TEPUNG SUKUN (Artocarpus communis) TERHADAP SIFAT SENSORIS DAN KIMIA BISKUIT - Dela Islaku; Gregoria S.S. Djarkasi; Yoakhim Y.E. Oessoe (COCOS, 2017)
ABSTRACTBreadfruit flour can be utilized as a food diversification material that can be processed into various products such as noodles, bread and biscuits. The addition of tapioca to the making of breadfruit biscuits is used as a thickening agent or a filler and binder in the manufacture of biscuits. The purpose of this study was to determine the exact amount of substitution of tapioca flour based on the sensory properties and chemical properties of breadfruit biscuits. This research uses Completely Randomized Design (RAL) with substitution of breadfruit flour and tapioca flour. The study was conducted with 3 replications and analyzed using a variety of scans (Anova). Influential treatment was carried out by BNT advanced test. The substitution treatment formulation is as follows: A (100% Flour Bread), B (95% Flour + 5% Tapioca Flour), C (90% Flour + 10% Tapioca Flour), D (85% Flour + 15 % Tapioca Flour), E (80% Flour + 20% Tapioca Flour). Parameters observed for water content, ash content, protein content, fat content, carbohydrate, caloric value and sensory properties. The result of the research showed that the treatment of D is biscuit with 85% breadfruit flour and 15% tapioca flour is the preferred biscuit panel with the hardness of biscuit 16.00 mm / g / second, water content 3,44%, ash content 2,92%, Fat content 11,87%, protein content 3,74%, carbohydrate 78,03%, and calorific value 433,91 kcal.Keywords: Biscuit, Breadfruit Flour and Tapioca Flour